2013
DOI: 10.1038/cddis.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C δ in ER stress and apoptosis induced by oxidized LDL in human vascular smooth muscle cells

Abstract: During atherogenesis, excess amounts of low-density lipoproteins (LDL) accumulate in the subendothelial space where they undergo oxidative modifications. Oxidized LDL (oxLDL) alter the fragile balance between survival and death of vascular smooth muscle cells (VSMC) thereby leading to plaque instability and finally to atherothrombotic events. As protein kinase C δ (PKCδ) is pro-apoptotic in many cell types, we investigated its potential role in the regulation of VSMC apoptosis induced by oxLDL. We found that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 36 publications
(45 reference statements)
1
60
0
1
Order By: Relevance
“…ox-LDL induces ROS in VSMC [8,9,10]. Therefore, we examined whether ox-LDL would induce CyPA secretion by Western blot analysis of CM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ox-LDL induces ROS in VSMC [8,9,10]. Therefore, we examined whether ox-LDL would induce CyPA secretion by Western blot analysis of CM.…”
Section: Resultsmentioning
confidence: 99%
“…CyPA can be secreted from RASMC in response to the ROS inducer LY83583 [11,12]. ox-LDL, as a proatherogenic factor, induces intracellular production of ROS in various cell types such as VSMC [8,9,10] and macrophages [26,27,28]. It has been reported that ox-LDL induces CyPA secretion from THP-1 via an unknown mechanism [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were identified as VSMC by their characteristic hill-andvalley growth pattern and immunohistochemistry for VSMC-specific β-actin. The primary cultured human VSMC were used to generate an immortalized cell line by using SV40T antigen, SV40T-expressing human VSMC retain expression of contractile phenotype markers including smooth muscle β-actin and smMHC to passage 10 and higher as we previously described [6]. For all experiments passage 7-17 SV40T-expressing human VSMC culture were used.…”
Section: Cell Culturementioning
confidence: 99%
“…Apoptosis is regulated in VSMCs by interactions between the local cells and cytokine environment within the arterial wall, and the expression of pro-and anti-apoptotic proteins by the cells (Bennett, 1999). Oxidized low-density lipoprotein (oxLDL), an atherogenic substance commonly present in atherosclerotic lesions, induces apoptosis in cultured VSMCs (Uchida et al, 2013;Larroque-Cardoso et al, 2013), endothelial cells (Dimmeler et al, 1997), and macrophages (Hardwick et al, 1996). The pathway for oxLDL-induced apoptosis includes activation of a complex cascade of kinases and changes in expression of Bcl-2 family genes (Cheng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%